The effect of storage tank material and condition on biodiesel blend B10 stability - Narasimmanaidu, Satishwara Rao (2024)
Biodiesel is made from organic materials such as animal fat, plant lipids and waste cooking oil; it is widely used in many applications such as in diesel engine. This is because biodiesel reduces the emissions of carcinogenic compounds compared to petrodiesel. However, the storage stability of biodiesel can be affected by storage tank materials and storage conditions such as extended storage period and different storage environment. On a related note, manual biodiesel storage monitoring system increases risk of human errors, operational cost and expensive. Therefore, this study aimed to investigate the effect of storage material and storage condition, and also foam insulation on biodiesel stability. This study also analysed the potential of IoT technique as a new method to monitor biodiesel stability. Two setups were considered for B10 fuel: a pilot test without storage insulation and an actual test with storage insulation. The pilot test was conducted using three biodiesel storage tank materials with various shapes: stainless steel, high-density polyethylene (HDPE) and glass. The actual test used HDPE and glass for storage material which were insulated with 3D printed foam, together with rockwool as comparison; B10 fuel in the glass storage tank was remotely monitored using IoT. Both setups were monitored in enclosed space (indoor temperature) and outdoor (sun exposure). Based on the pilot test data collected, the results indicated that fuel samples barely degraded in indoor conditions. Properties of fuel in stainless steel tank stored outdoor for 90 days increased by 1.57%, 0.88%, 54.92% and 47.46% in density, kinematic viscosity, water content, and acid value, respectively. Meanwhile, the fuel samples stored outdoor in clear glass tanks showed dramatic increases in density, kinematic viscosity, water content and acid value by 4.35%, 11.23%, 95.08% and 95.41%, respectively, within 90 days of storage. However, the flashpoint decreased by 5.26% with increasing storage duration. Besides that, 3D printed foam as insulation for storage tanks was crucial as the degradation rate dropped for all biodiesel properties when compared to pilot test data. Fuel samples stored in the glass tank with foam insulation increased steadily by 1.69%, 4.67%, 68.85%, and 63.22% for density, kinematic viscosity, water content, and acid value, respectively, after 90 days storage. Furthermore, shapes of storage tank did not have an impact on experimental investigations. CFD simulation was conducted on storage tank insulations which managed to reduce temperature distribution of outdoor exposure (31.3ºC) within the insulator before reaching storage tank wall for rockwool (28.8ºC) and printed foam (29.7ºC). Moreover, RSI value obtained for rockwool and printed which were 1.55 and 1.2, respectively. Meanwhile, IoT monitoring system recorded pH values in the range of 7.02 to 7.22 for indoor glass storage tank; these pH values were also manually validated using pH strips. However, pH values of the outdoor fuel samples dropped from pH 7 to pH 5 indicating increases in acid value within 90 days. From this study, it has been shown that biodiesel stability can be affected by storage material and storage condition; storage tanks made from stainless steel managed to reduce biodiesel degradation and is recommended as a storage tank material for B10, while higher storage temperature and longer storage duration result in biodiesel degradation. Foam insulation is shown to be an effective way to slow down biodiesel degradation. IoT technique is also demonstrated as a reliable new method to monitor biodiesel stability.